2022
DOI: 10.1111/jan.15188
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of contracting COVID‐19 in nursing homes: Implications for clinical practice

Abstract: Aims The aim of the study was to identify the predictors of contracting COVID‐19 among older people in nursing homes in Iran. Design A case–control study. Methods Four‐hundred‐nine nursing home residents aged 60 years and above, with a 1:2 ratio of those infected with SARS‐CoV‐2 to those not infected, from six nursing homes in Tehran between 25 March and 12 July 2021 were recruited. Participants completed a questionnaire comprising demographic and underlying disease questions, practice about prevention princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…In particular, the postintervention trend demonstrated a 27% decrease in the COVID-19 incidence rate every 2 days (RR,0.73; 95% CI, 0.67–0.80; p < 0.001) NR NR In British Columbia, 59% of COVID-19– related deaths were in LTCFs, compared to 75% in Canada overall and 30%–60% across Europe Our study provides evidence for the effectiveness of this intervention to reduce the transmission of COVID-19 in LTCFs. This intervention can be adapted and utilized by other jurisdictions to protect the vulnerable individuals in LTCFs Aghili et al 2022 [ 34 ] Iran Case–control study To identify the predictors of contracting COVID-19 among older people in nursing homes in Iran From 25 March to 12 July 2021 6 409 residents Cases : 136 residents Covid + Control : 273 residents Covid- Cases : 136 Control :273 covid- NR NR There are no formal statistics about the mortality rate due to COVID-19 in nursing homes in Iran. Nursing homes are predominantly non-government-owned organizations that are authorized, supervised and funded by the State Welfare Organization of Iran The results indicate that an increase in older people becoming infected by SARS-CoV-2 in nursing homes is probably because of not wearing a mask in common places, use of a cloth mask, longer staff shift durations and not having a glass shield when interacting with visitors from outside of nursing homes Telford et al, 2021 [ 35 ] USA Case–control study Determine the efficacy of recommendations for infection prevention and control of COVID-19 in LTCF for reducing transmission among high-risk populations June and July 2020 24 24 LTCF Cases: 11 LTCF, 1310 residents Higher-prevalence group (HPG) (infection prevalence among residents greater than the overall infection proportion (39%)) Control: 13 LTCF, 1270 residents—Lower-prevalence group (LPG) (infection prevalence lower than the overall proportion) Cases : HPG – 817 Control : LPG – 187 Cases :HPG124 Control : LPG – 38 Cases : HPG – 196 Control : LPG – 51 Fulton County, Georgia, which covers the city of Atlanta, had received reports of 1,183 C...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the postintervention trend demonstrated a 27% decrease in the COVID-19 incidence rate every 2 days (RR,0.73; 95% CI, 0.67–0.80; p < 0.001) NR NR In British Columbia, 59% of COVID-19– related deaths were in LTCFs, compared to 75% in Canada overall and 30%–60% across Europe Our study provides evidence for the effectiveness of this intervention to reduce the transmission of COVID-19 in LTCFs. This intervention can be adapted and utilized by other jurisdictions to protect the vulnerable individuals in LTCFs Aghili et al 2022 [ 34 ] Iran Case–control study To identify the predictors of contracting COVID-19 among older people in nursing homes in Iran From 25 March to 12 July 2021 6 409 residents Cases : 136 residents Covid + Control : 273 residents Covid- Cases : 136 Control :273 covid- NR NR There are no formal statistics about the mortality rate due to COVID-19 in nursing homes in Iran. Nursing homes are predominantly non-government-owned organizations that are authorized, supervised and funded by the State Welfare Organization of Iran The results indicate that an increase in older people becoming infected by SARS-CoV-2 in nursing homes is probably because of not wearing a mask in common places, use of a cloth mask, longer staff shift durations and not having a glass shield when interacting with visitors from outside of nursing homes Telford et al, 2021 [ 35 ] USA Case–control study Determine the efficacy of recommendations for infection prevention and control of COVID-19 in LTCF for reducing transmission among high-risk populations June and July 2020 24 24 LTCF Cases: 11 LTCF, 1310 residents Higher-prevalence group (HPG) (infection prevalence among residents greater than the overall infection proportion (39%)) Control: 13 LTCF, 1270 residents—Lower-prevalence group (LPG) (infection prevalence lower than the overall proportion) Cases : HPG – 817 Control : LPG – 187 Cases :HPG124 Control : LPG – 38 Cases : HPG – 196 Control : LPG – 51 Fulton County, Georgia, which covers the city of Atlanta, had received reports of 1,183 C...…”
Section: Resultsmentioning
confidence: 99%
“…The studies do not agree on the importance of the number of beds per room. Some results show that the number of beds per room has no significant association with the COVID-19 spread [ 34 , 38 , 39 , 44 ]. However, others show that double or quadruple-occupancy rooms (with shared bathrooms) promote COVID-19 dissemination (compared with LTCF with single rooms, had double the COVID-19 incidence (relative risk [RR], 2.05; 1.49–2.70) and is associated with COVID-19 mortality (RR, 1.97; 1.36–2.84)) [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty-seven studies reported on the effectiveness of masks for reducing transmission of SARS-CoV-2 as their primary outcome: 24 studies (two RCTs, 22 observational) in community settings [14][15][16][17][18]20,21,23,[25][26][27]29,33,34,[36][37][38][39][40][41]43,44,46,48] and 23 observational studies in healthcare settings [50,[53][54][55][56][57][58][59][60][61][63][64][65][66]68,69,[75][76][77]81,82,84,85].…”
Section: (A) Masks For Reducing Transmission Of Sars-cov-2mentioning
confidence: 99%
“…Nineteen studies compared the effectiveness of different types of masks for reducing transmission of SARS-CoV-2: four studies (two RCTs, two observational) in community settings [14,16,23,47] and 15 studies (one RCT, 14 observational) in healthcare settings [50,52,57,68,[70][71][72][73][74]78,80,[82][83][84]88].…”
Section: (B) Comparative Effectiveness Of Different Types Of Masksmentioning
confidence: 99%